2023
DOI: 10.3390/membranes13080706
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Precursor Protein Changes Arrangement in a Membrane and Its Structure Depending on the Cholesterol Content

Vladimir D. Krasnobaev,
Yaroslav V. Bershatsky,
Olga V. Bocharova
et al.

Abstract: One of the hallmarks of Alzheimer’s disease (AD) is the accumulation of amyloid beta (Aβ) peptides in the brain. The processing of amyloid precursor protein (APP) into Aβ is dependent on the location of APP in the membrane, membrane lipid composition and, possibly, presence of lipid rafts. In this study, we used atomic force microscopy (AFM) to investigate the interaction between transmembrane fragment APP672–726 (corresponding to Aβ1–55) and its amyloidogenic mutant L723P with membranes combining liquid-order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…The extent to which liquid-ordered and liquid-disordered (L d ) domains coexist in cell membranes, or even the mere existence of liquid-ordered (L o ) domains in cells, is still an object of debate [ 29 , 30 , 31 , 32 , 33 ]. For the specific case of Aβ–membrane interactions, Krasnobaev et al [ 7 ] observed, using atomic force microscopy, that transmembrane fragment APP672-726 (corresponding to Aβ1-55) is located either in the L d phase or at the boundary between ordered and disordered phases but not in L o domains. We already observed that L d bilayers consistently allowed a higher Aβ(1-42) binding than L o ones [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extent to which liquid-ordered and liquid-disordered (L d ) domains coexist in cell membranes, or even the mere existence of liquid-ordered (L o ) domains in cells, is still an object of debate [ 29 , 30 , 31 , 32 , 33 ]. For the specific case of Aβ–membrane interactions, Krasnobaev et al [ 7 ] observed, using atomic force microscopy, that transmembrane fragment APP672-726 (corresponding to Aβ1-55) is located either in the L d phase or at the boundary between ordered and disordered phases but not in L o domains. We already observed that L d bilayers consistently allowed a higher Aβ(1-42) binding than L o ones [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent studies, when a pure Aβ(1-40) peptide was mixed with monolayers of dipalmitoyl phosphatidylcholine (DPPC), which is known to undergo a temperature- and lateral pressure-dependent liquid-expanded-to-liquid-condensed bidimensional phase transition, the fibril-like structure of Aβ(1-40) appeared specifically in the liquid-expanded region [ 6 ]. Krasnobaev et al [ 7 ] used atomic force microscopy (AFM) to study the interaction of Aβ(1-55) with membrane bilayers containing liquid-ordered (L o ) and liquid-disordered (L d ) lipid domains. Most of the peptide was found either in the L d phase or at the boundary between ordered and disordered phases, in agreement with the data from Alvarez et al [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation